Luminescence at low temperature in pure ZnO phosphors (2020)
(Eng) In this paper, samples of pure ZnO were prepared through solid - state chemical reaction, and optical spectral properties were investigated at low temperature. It was found that the strong broad band emission was shifted to the blue side with increase of temperature. It is tentatively attributed to the ch ange of local electric field from electric dipoles, orientation of which is sensitive to temperature. The ultraviolet sharp lines observed at low temperatures are assigned to bound excitons and their phonon replicas.